Mechanical characterization of particulated FRP composite pipes: A comprehensive experimental study - Farrukh Saghir (Elsevier, 2021)
Particulated fiber reinforced polymer (FRP) composite pipes encompass unidirectional continuous glass fibers (hoop glass), resin (thermoset polymer vinylester) matrix, chop glass (discontinuous short fibers), and particulate reinforcement (sand) impregnated into resin. They are categorized based on their nominal diameter, pressure class, and stiffness class. Mechanical characteristics of this class of composite materials have not, to date, been comprehensively studied. As such, this paper presents a systematic approach toward comprehensive experimental investigation into their mechanical characterizations in terms of the axial and hoop tensile strengths. The particulated FRP composite pipes used in the current study have glass fibers reinforced along the hoop direction at approximately 89° angle. To assure the experimental data accuracy and reliability, three batches associated with each pipe category were selected which slightly differ in the composition of their constituents. Three specimens per batch were selected and two types of tests were conducted on each specimen. 18 tests (2 × 3 batches × 3 specimens)) were conducted per pipe category (9 tests for hoop and 9 tests for axial). Therefore, 648 tests were conducted in total on 36 pipe categories. Instron 5569A and Instron 8801 universal testing machines were utilized for the axial tensile tests and a split disc hydraulic testing machine for the hoop tensile tests. The mean tensile and the hoop axial stresses and their associated standard deviations were calculated based on the Population Standard Deviation (PSD) equation and then plotted against the material constituents. The results demonstrated that an increase in the composition of particulate reinforcement results in a decrease in the axial and the hoop tensile strengths. However, increasing the ratio of resin, chop glass, and glass fibers contributes to the enhancement of the axial and the hoop tensile strengths. This study provides comprehensive design guidelines for engineers and manufacturing industries.